2014
DOI: 10.1002/pd.4385
|View full text |Cite
|
Sign up to set email alerts
|

Overview of low molecular weight heparin for preventative treatment of adverse obstetric outcomes related to abnormal placentation

Abstract: Different proportions of cases of preterm and severe preeclampsia, placental abruption, fetal growth restriction, and fetal death share a common causal pathway of abnormal placental implantation. Documentation of an association between the risk of such adverse pregnancy outcomes (APOs) and inherited thrombophilias prompted initial studies to evaluate the benefit of anticoagulants for the prevention of recurrences both in patients with and without inherited thrombophilias. Prenatal administration of low molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…In the interim, important information may be gleaned from complement inhibitors already in use (e.g., eculizumab) or existing agents with anti-complement effects such as heparin (Garlatti et al, 2010; Girardi et al, 2004; Oberkersch et al, 2010). Heparin, unfractionated or low molecular weight, appears to decrease the recurrence of placentally-driven adverse pregnancy outcomes (Ghidini, 2014; Kupferminc et al, 2011) and may improve live birth rate in APLAS (Girardi et al, 2004; Rai et al, 1997). Until additional complement therapeutics become readily available, it may be helpful to investigate the anti-complement effects of heparin in pregnancy to better understand the role of complement blockade in reducing adverse pregnancy outcomes.…”
Section: Therapeutic Manipulation Of the Complement System In Pregmentioning
confidence: 99%
“…In the interim, important information may be gleaned from complement inhibitors already in use (e.g., eculizumab) or existing agents with anti-complement effects such as heparin (Garlatti et al, 2010; Girardi et al, 2004; Oberkersch et al, 2010). Heparin, unfractionated or low molecular weight, appears to decrease the recurrence of placentally-driven adverse pregnancy outcomes (Ghidini, 2014; Kupferminc et al, 2011) and may improve live birth rate in APLAS (Girardi et al, 2004; Rai et al, 1997). Until additional complement therapeutics become readily available, it may be helpful to investigate the anti-complement effects of heparin in pregnancy to better understand the role of complement blockade in reducing adverse pregnancy outcomes.…”
Section: Therapeutic Manipulation Of the Complement System In Pregmentioning
confidence: 99%
“…Maternal immune system could then be modulated in order to reduce the risk of adverse pregnancy outcomes in these patients using prophylactic treatments such as progesterone or low molecular weight heparin. Immunomodulatory prophylactic interventions have been used to prevent preterm labour, 46 adverse obstetric outcomes related to abnormal placentation 47 and recurrent pregnancy loss 48 . MBL seems to play different roles in various pregnancy pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…Because interventions after the diagnosis of the clinical manifestations of preterm APOs have limited impact on the outcome, it has become clearer that the optimal timing for interventions should be much earlier in pregnancy, namely, at the time of placental implantation. Randomized clinical trials have shown that prophylaxis using low‐molecular‐weight heparin in women with history of preterm and severe APOs can be effective at reducing recurrences, with little heterogeneity among the studies . Similarly, low‐dose aspirin has been shown to effectively reduce the risk of preterm APOs (more effectively for preeclampsia than FGR) not only in pregnancies flagged by a poor obstetric history but also in those identified prospectively by abnormal uterine artery Doppler findings .…”
Section: Preventionmentioning
confidence: 99%